Bibliography on Land-Locked States: Fourth Revised and Enlarged Edition - Glassner, M.I. (BIBLIOGRAPHY ON LAND-LOCKED STATES: Fourth Revised and Enlarged Edition, 2023)
Keywords: dept.egm

Blue Economy - Germond-duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2023)
Keywords: dept.egm

Breaking wind: A comparison between U.S. and European approaches in offshore wind energy leadership in the North Atlantic region - Gallaher, Adam; Graziano, Marcello; Axon, Stephen; Bertana, Amanda (Renewable and Sustainable Energy Reviews, 2023)
The United States has only recently begun investing in commercial-scale offshore wind energy (OWE). Although the United States is slow to progress, it is uniquely positioned to build on the existing knowledge that coastal European countries have applied for their own energy transitions. In this study, we analyze how federal and regional plans for expanding the OWE sector in the United States brought to the surface decade-long tensions related to multi-scale governance mismatches, jurisdictional conflicts, and unclear pathways for implementing national industrial policies. Drawing upon the European experience with OWE, we employ a dynamic multi-level perspective framework enriched by socio-ecological elements to examine the United States energy transition through its most promising technology. From our framework we identify six categories of OWE developments characterized by both unique and shared elements between the United States and European coastal countries. These elements are: (1) role of local communities, (2) governance structures, (3) multi-scale government interactions, (4) regional socioeconomic structures, (5) socio-ecological impacts, and (6) relationships with existing industries. Drawing upon our analysis, we identify and conceptually map four research areas in need of further development for the United States and the research community— (1) knowledge, (2) potential, (3) adaptation, and (4) learning. These insights provide critical information to ensure that the United States expansion into offshore energy generation is characterized by elements of justice, equity, and inclusive regional economic development.
Keywords: Blue economy; Comparative analysis; Just energy transitions; Multi-level perspective; Offshore wind energy; dept.egm; dept.soc; peer-reviewed

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

Breaking Blue: Establishing comprehensive policy for a just and inclusive transition for the Blue Economy - Axon, Stephen; Collier, Sammy (Marine Policy, 2023)
At a time of substantial interest in the Blue Economy, it is surprising that sustainability dilemmas and justice components are not well integrated within its academic discourse or policy arena. Reviewing a number of existing U.S. coastal and marine policies, we identify that justice and equity components are essentially missing and advocate for a comprehensive policy framework for a just and inclusive transition for the Blue Economy. Looking forward, we review and critique the policy proposal of Elizabeth Warren’s Blue New Deal. While the current state of the Blue New Deal remains uncertain, we indicate that such a policy framework would integrate justice, equity and inclusivity as part of operationalising the Blue Economy. Given the proposal for a Blue New Deal is relatively new, we propose a research agenda to explore how comprehensive policy frameworks may seek to place justice and inclusivity at the centre of the Blue Economy.
Keywords: Blue Economy; Blue Justice; Blue New Deal; Governance; Sustainability; dept.egm; peer-reviewed